Effect of ultrasound and microwave treatment on the level of volatile compounds, total polyphenols, total flavonoids, and isoflavones in soymilk processed with black soybean (Glycine max (L.) Merr.) - Minju Lee; Kwang-Geun Lee (Ultrasonics Sonochemistry, 2023)
This study analyzed the effect of ultrasound treatment (up to 9 min, 20 kHz, 130 W) on the volatile compounds, total polyphenols, total flavonoids, and isoflavones (daidzein, genistein, daidzin, genistin, and glycitin) in soymilk processed with microwave-roasted (700 W for 270 s) black soybean (Glycine max (L.) Merr.). 1-Hexanol and 1-octen-3-ol, unpleasant soybean flavors, were found to decrease by up to 96.13% and 93.04%, respectively, in ultrasound-treated soymilk compared to the control. 2,3-Diethyl-5-methylpyrazine, a baked flavor, which exhibited the highest odor impact ratio in soymilk processed with microwave-roasted soybean, increased significantly during ultrasound treatment (p < 0.05). The content of total isoflavones, polyphenols, and flavonoids increased (p < 0.05) with the increase in ultrasound treatment time. Spearman's correlation analysis showed that browning was positively correlated (p < 0.01) with total phenols, total furans, total pyrazines, total polyphenols, and total isoflavones. This study discusses the applicability of microwave-roasted soybeans for improving the volatile profile and bioactive compounds in soymilk and provides information on the effects of ultrasound treatment on the volatile compounds, total polyphenols, flavonoids, and isoflavones in soymilk.